Benchmarking level interactivity of Indonesia government university websites - Nurdin Nurdin; Zana Chobita Aratusa (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
Website interactivity is increasingly essential for higher education institutions in maintaining their relationship with stakeholders. However, limited is known what the level interactivity of a university website is without comparing with other similar educational institutions. Through the use of website content analysis and benchmarking strategy, we evaluate 41 government university website for benchmarking purposes. Base on thirteen interactive criteria, we successfully benchmarked the government university websites and built a-five levels of websites interactivity with different features. Our study highlights that higher level interactivity of website contains more feature that support a two-way communication between university and consumers, while lower level of websites interactivity merely have basic features for communication. The findings suggest the highest level of websites interactivity, the more features they should have. More importantly, the findings suggest web developer to design more interactive features in developing a higher level of website interactivity.